1994
DOI: 10.1038/ki.1994.181
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA deletion: A cause of chronic tubulointerstitial nephropathy

Abstract: We report the first case of a mitochondrial DNA (mtDNA) deletion diagnosed by renal biopsy. An eight-year-old girl with megaloblastic anemia and severe growth retardation developed progressive renal insufficiency accompanied by partial Fanconi syndrome. Histologic examination of the renal biopsy disclosed nonspecific chronic tubulointerstitial disease characterized by tubular atrophy and interstitial fibrosis. On ultrastructural examination, tubular cell mitochondria were extremely dysmorphic with prominent si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 26 publications
4
41
3
Order By: Relevance
“…The most common manifestation is a proximal tubulopathy with de Toni-Debré-Fanconi syndrome (12,13). Other renal presentations have been reported, including glomerular disease with nephrotic syndrome and chronic tubulointerstitial nephropathy (14,15). Plasma lactate levels and lactate/pyruvate (L/P) ratios are consistently normal but, interestingly, abnormal urinary lactate and Krebs cycle intermediate levels indicate a RC deficiency.…”
Section: Mitochondrial Rc Disordersmentioning
confidence: 97%
“…The most common manifestation is a proximal tubulopathy with de Toni-Debré-Fanconi syndrome (12,13). Other renal presentations have been reported, including glomerular disease with nephrotic syndrome and chronic tubulointerstitial nephropathy (14,15). Plasma lactate levels and lactate/pyruvate (L/P) ratios are consistently normal but, interestingly, abnormal urinary lactate and Krebs cycle intermediate levels indicate a RC deficiency.…”
Section: Mitochondrial Rc Disordersmentioning
confidence: 97%
“…All the above-mentioned aspects make proximal tubules especially vulnerable to mitochondrial dysfunction, which leads to RTEC apoptosis/necrosis, EMT, and renal fibrosis. A case report showed that mtDNA deletion can lead to extremely dysmorphic mitochondria with defects in respiratory chain enzymes encoded by mtDNA in tubular cells, which clinically manifests as tubular atrophy and interstitial fibrosis (132).…”
Section: Acquired Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…(Figure 1), and one report describes an individual presenting with symptoms of Pearson Syndrome but developing features of Kearns-Sayre syndrome over time. 44 The renal tubular defects associated with mtDNA deletions may affect the proximal 40,[43][44][45][46][47] or distal renal tubular segments. 39 The rarity of reports that include mtDNA deletions and a kidney phenotype make it difficult to draw any genotype-phenotype correlations, and the factors that contribute to the variety and penetrance of clinical features associated with mtDNA deletions may be related to the inheritance and distribution of mtDNA, as discussed earlier.…”
Section: Mitochondrial Dna Deletionsmentioning
confidence: 99%